Dream Knowledge – Understanding the Dreamworld Utilizing the Medicine Wheel - John T. Ward (Journal of Global Indigeneity)
This article looks at Indigenous dreaming and spirituality, which brings healing, greater resilience, and has the power to heal trauma. Analyzing dreams or ‘dream weaving’ is a conduit with a message that brings about healing and well-being (Lorenz, 2013; Riley-Mukavetz, 2021). To understand Indigenous dream culture, the Medicine Wheel is an essential tool for guiding one’s development – a methodology for understanding humanity and obtaining holistic guidance. There are many ways to use it, as it is a paradigm method used when teaching circle pedagogy. This sacred circle (Couture, 2011) provides a balance in spiritual and health connections that gives all members a chance to explain and debate, prior to determining a cause of action. Many ways exist of interpreting dreams, but it also necessary to focus on the wisdom and knowledge of Elders and others as guides, who are familiar with Indigenous spiritual perspectives. This article thus includes an evaluation of dreams, dream knowledge and a study of the use of the Medicine Wheel, along with spirituality. This dream knowledge presented reflects my own lived experience as an educator of settler-Indigenous background, as I use dreams to interpret my own spiritual, emotional, physical, and mental well-being.